Numerical analysis of compression strength in network structures based on trusses, and periodic surfaces aimed for additive manufacturing - Jansson, Anton (2018)
In this paper, the compressive response for a number of truss- and surface-based networks with equal relative density was compared. The effect of errors in the structures were also investigated. The results show that surface networks are, in general, more efficient structures than truss-lattices in compression. The results also show that surface networks are significantly more resilient to fabrication errors than their truss-lattice counterparts.